Testing the relationships between motivation and future intention in physical activity: does governmental financial support matter?. Issue 3 (3rd July 2019) - Kwon, Hyungil H.; Pyun, Do Young; Kim, Ji Young
ABSTRACT: As a new sports policy, named "School Sport Promotion Group (SSPG)", the Korea government selected 50 schools in 2011 and 2012. Each school was granted US$40, 000 a year for a three-year term. The purpose of this study was to examine the effectiveness of the SSPG programme when it pertained to students' motivation and participation in school sport clubs. More specifically, the moderation effect of governmental financial support in the relationships between motivation (intrinsic and extrinsic) and sport participation was tested using structural equation modelling. The results indicated that both intrinsic motivation ( β  = .22) and extrinsic motivation ( β  = .20) were significant indicators of future participation intention in a non-SSPG model while only intrinsic motivation ( β  = .58) was a significant indicator in the SSPG model. A chi-square differential test showed that the coefficient of the path from intrinsic motivation to future intention in the SSPG was significantly larger than that in the non-SSPG model, supporting the moderating role of governmental financial support. The results of this study can provide administrators with meaningful information regarding how financial support can promote students' physical activity and health.